Estimating Relative Attractiveness of Locations using Multiple Attribute Decision Making (MADM) (Journal of Informatics and Mathematical Sciences, 2011)
Competitive facility location problems involve identifying the best location of facility that can capture maximum market share in the presence of competition. One of the most popular models for competitive facility location, namely the Huff model is not considered very realistic and efforts have been made to improve the model by including additional factors. In this paper, an extension of Huff model to consider multiple factors using multiple attribute decision making (MADM) is proposed. MADM problem is a management science technique, which is popularly used to rank the priority of alternatives with respect to their competing attributes. Weights from the core of MADM: it is obvious that different weight lead to various evaluation results and decisions. The proposed model is applied for estimating the market share.
Keywords: Competitive facility location; The Huff model; Multiple attribute decision making (MADM)